Effect of Anthropogenic Activities on Patterns of Genetic Diversity in Symplocos racemosa Roxb. from Western Ghats, India. (11th February 2014) - Banu, Sofia; Bhagwat, Rasika M.; Lagu, Meena D.; Kadoo, Narendra; Kulkarni, B. G.; Gupta, Vidya S.
Abstract : The Western Ghats (WG) in India is recognized as one of the global biodiversity hotspots which have high proportion of endemic species and the medicinally important tree species. Due to medicinal importance and being found on the forest fringes, Symplocos racemosa Roxb. is highly susceptible to anthropogenic activities. The present study was undertaken to systematically analyze the effects of anthropogenic activities on the genetic diversity and population structure of S. racemosa and to generate preliminary data for conservation purposes. We analyzed the variation in intergenic sequences of chloroplast and mitochondrial genomes from seven sites of S. racemosa sampled from protected, semiprotected, and disturbed areas of WG. Total diversity was high although within-sites diversity was low. The protected sites were highly diverse, while the disturbed areas possessed less genetic diversity indicating the effect of anthropogenic activities.